Monuments, unreal spaces and national forgetting: Kazuo Ishiguro's The Buried Giant and the abyss of memory. Issue 4 (3rd April 2023) - Teo, Yugin
ABSTRACT: At the announcement of Ishiguro's 2017 Nobel Prize in Literature award, his writing was described as having 'uncovered the abyss beneath our illusory sense of connection with the world'. Uncovering this abyss entails a confrontation between characters, communities, and the complex relationship with their pasts. Ishiguro's decision to engage with memory on a national scale sees a renewed focus on the theme of forgetting in his oeuvre, and a critical exploration of the multiple layers of collective memory. Ishiguro's text urges the reader to consider the ethical complexities of memorialisation and enforced amnesty. This essay establishes The Buried Giant as a key development within Ishiguro's long-standing memory work, signalling a more considered engagement with themes of shared memory and national identity, as well as the politics of memorialisation, confirming the novel's significance as a focal point on discussions of collective and individual memory within contemporary literature.